Gen-Z and green banking adoption in Yogyakarta, Indonesia: Evidence from a PLS-SEM survey - Rahayu, Ninik Sri; Hidayat, Ahmad Rifqi (The Economics and Finance Letters, 2026)
The study investigated the determinants of Generation Z's intention to adopt green banking using four variables: financial literacy, sustainability literacy, green banking intention, with trust serving as a mediating variable. Generation Z was selected as the target group due to their high awareness of environmental issues and advanced digital skills, which may make them more receptive to eco-friendly efforts such as green banking. A digital survey in 2024 focused on the youth of Yogyakarta, Indonesia. Of the distributed questionnaires, 417 valid responses were collected, resulting in a response rate of 40%. The data was analyzed using PLS-SEM. The results demonstrate that financial literacy substantially affects both sustainability literacy (β = 21.255, p = 0.000) and trust (β = 11.261, p = 0.000), which consequently influence green banking intention. Additionally, financial literacy directly encourages green banking adoption (β = 4.006, p = 0.000), while trust primarily acts as a determinant in bridging financial literacy and intention to act (β = 11.262, p = 0.000). The findings can assist policymakers and SDG adopters in engaging post-millennials as key actors for promoting the UN sustainable development framework and spreading eco-literacy within their communities at various levels.